Redistribution Policy in Europe and the United States Is the Great Recession a 'Game Changer' for Working-age Families? - Immervoll, Herwig (OECD Publishing, 2013)
Working-age individuals and their families have experienced increases in relative income poverty before the Great Recession (GR), and they have also seen significant income losses since the beginning of the downturn in 2007/8. This paper examines the effects of benefit and tax reforms on the distribution of incomes of non-elderly individuals in Europe and in the United States both before and after the GR. We aim to place recent policy responses in context of both the broader trends in redistribution patterns observed since the 1980s, and the immediate crisis-related challenges, including a much greater need for government support, and large and rapidly growing government debt. Analysis of historical household income data confirms the common finding that redistribution reduces income inequalities by much less in the US than in much of Europe. Since more redistributive tax-transfer systems tend to be more effective as a backstop to widening earnings gaps, redistribution in the US was also less effective at offsetting the substantial increase in the market-income inequality in the 2-3 decades leading up to the GR. Focussing on more recent policy changes, we then calculate income gains and losses that can be attributed to reforms shortly before and after the GR at different points in the earnings spectrum. The results show that a combination of discretionary and automatic policy changes in the US have significantly narrowed the pre-GR gap between the equalising capacities of US and European redistribution measures, and between their abilities to cushion the effects of economic shocks on household income. We argue, however, that this is unlikely to signify any longer-term convergence, and that Europe/US comparisons need to go beyond the common focus on differences in redistribution levels. In our view, an equally important question is how well redistribution measures respond and adapt to evolving social and fiscal challenges at different points in the economic cycle
Keywords: Social Issues/Migration/Health; European Union; United States